Księgozbiory wybranych bibliotek klasztornych braci kaznodziejów w Polsce w XVII w. na podstawie zachowanych inwentarzy - Stolarczyk, Tomasz (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The aim of hereby article is to present the epitome of Dominican Convent libraries situated within the area of the former archdeaconry of Łęczyca: in Gidle, Łęczyca, Łowicz, Piotrków Trybunalski and Sieradz, as well as their book collection originating from XVII century. They were functioning since the monasteries were funded the evidence of what is existence of Dominican schools which could not do without libraries. The extra thought was given to the books at the Order of Preacher Brethren, which is expressed in its legislation. Disobedience to the library rules resulted in severe consequences including excommunication. The analysis of the mentioned book resources was carried out on the basis of Latin library inventories from the 17th century, which were included in the codex of Preacher Brethren of Łęczyca, Łowicz and Piotrków and Gidle inventory created in the beginning of XX century. All those inventories are now stored in the archives of the Polish Province of Dominicans in Kraków. The largest book collection was in the possession of Sieradz Dominicans –about 400 volumes. The second largest collection was in Gidle library with 345 volumes. On the third position was the library of Łowicz Convent which collection comprised 294 volumes. The fourth biggest library was the library in Piotrków which stored 215 volumes. In the Łęczyca library there were about 100 volumes in the beginning of XVII century.